PENGARUH KUALITAS PELAYANAN DAN KESELAMATAN WISATAWAN TERHADAP KEPUASAN WISATAWAN DI DAYA TARIK WISATA AIR TERJUN TEGENUNGAN GIANYAR BALI - Binawa, I Gede Putra; Indrawati, Yayu; Mananda, I Gusti Putu Bagus Sasrawan (Jurnal Ilmiah Global Education, 2023)
The purpose of conducting this research was to analyze the effect of service quality and tourist safety on tourist satisfaction at Tegenungan Waterfall Gianyar Bali. The number of samples used in this study were 65 people. Using accidental sampling method. Collecting data using library research, observation, questionnaires and interviews. The data analysis technique used is multiple linear regression using the SmartPLS application. The results of this study indicate that service quality has a significant effect on tourist satisfaction. This shows that respondents' perceptions of service quality have a strong correlation with tourist satisfaction when visiting Tegenungan Waterfall Gianyar Bali. Tourist safety has a significant effect on tourist satisfaction, where the tourist safety perceived by respondents in the form of providing an explanation to tourists before entering the waterfall area correlates with perceived tourist satisfaction with a sense of satisfaction with the services provided by the manager of the Tegenungan Waterfall. The implications of this research are Service Quality Improvement, Safety Priority and Tourist Feedback.